Microstructural characterization and mechanical properties of additively manufactured molybdenum and molybdenum alloys. (December 2022) - Oehlerking, Faith; Stawovy, Michael T.; Ohm, Scott; Imandoust, Aidin
Abstract: Molybdenum (Mo) and its alloys are one of the refractory material groups of interest for additive manufacturing (AM), as they meet the requirements for some applications in aerospace and medical industries. The present research and development work aims to develop the proper parameter sets for pure Mo and its alloys, such as Mo-47.5Re wt% and characterize their microstructure and mechanical properties. Primary parameter optimization of the laser power, point distance, exposure time, and hatch distance were tested using a design of experiments to optimize the relative density of the specimens for the Laser Powder Bed Fusion (L-PBF) metal AM technology. Test specimens with relative densities of >98% were successfully fabricated for both pure Mo and Mo-47.5Re wt%. Mechanical testing and microstructural characterization were conducted on the specimens. Microcracking is present in both pure Mo and Mo-47.5Re wt%. Persistence of cracking in the Re containing alloy can be attributed to higher concentration of oxygen in the fabricated samples. A significant increase in strength and compressive ductility was observed in AM fabricated Mo-47.5Re wt% as compared to the pure Mo samples. Solidification texture randomization was also observed in Mo-47.5Re wt%, for which the underlying mechanism is not yet understood. This provides an encouraging outlook to continue testing and developing Mo and its alloys on a L-PBF platform with further stress reduction and material development strategies. Highlights: After parameter development, pure Mo and Mo-47.5Re wt% alloy samples and demo parts were printed with relative densities of 98.5 and 99.4%, respectively. Grain boundary cracking was observed in both materials in as-built and stress-relived conditions, while Re showed shorter crack lengths. Mo-47.5Re wt% alloy showed a significant improvement in mechanical strength and compressive plasticity. Re containing samples showed randomized texture as compared to pure Mo, which could be another contributing factor for their enhanced plasticity.